Pengaruh Brand Image, Price Dan Trust Terhadap Purchase Intention Pemesanan Kamar Di Hotel Ibis Secara Online - Selvi Agustin (Universitas Tarumanagara, 2019)
This research was conducted to analyze the influence of brand image, price and trust toward purchase intention of room booking at Ibis hotel via online method. Independent variables that were researched are brand image, price and trust. Meanwhile, dependent variables that were researched is purchase intention. The population that was researched is consumers who have stayed at Ibis hotel and used online booking method. Sampling used nonprobability method with non-probability sampling. Data collection method used questionnaires which were distributed to 135 respondents who have stayed at Ibis hotel and used online booking method. Data analysis technique that was used is double regression analysis. The analysis result shows that there is an influence from price and trust toward purchase intention. However there is no influence from brand image toward purchase intention and the impact of brand image it is not significant. This research result is expected to be able to be used as a reference for online hotel booking marketer in Indonesia in order to attract tourists when they use online hotel booking.